Antecedents of brand image: A conceptual model - Wasib, Latif; Md. Aminul, Islam; Mahadzirah, Mohamad (2015)
The antecedents of brand image are defined as the differential effect of brand knowledge on customer response to marketing of the brand. It is now widely acknowledged by organizations that strong brand image will create a competitive advantage in the marketplace that will enhance their overall reputation and credibility. Indeed, study of antecedents of brand image is increasingly becoming significant in modern marketing. In this conceptual paper, we have summarized the literatures on currently prevailing concepts and approaches on brands that will allow us to identify the antecedents of brand image, and therefore will help organizations to enhance their marketing efficiency. Based on a comprehensive review of several earlier works, here we propose a plausible model for the antecedents of brand image in sequential order, namely, awareness of the brand, association of the brand, superiority of the brand, affection of the brand, resonance of the brand and corporate social responsibility.